Cognition in patients with neuromyelitis optica spectrum disorders: A prospective multicentre study of 217 patients (CogniNMO-Study). (June 2023) - Hümmert, Martin W; Stern, Carlotta; Paul, Friedemann; Duchow, Ankelien; Bellmann-Strobl, Judith; Ayzenberg, Ilya; Schwake, Carolin; Kleiter, Ingo; Hellwig, Kerstin; Jarius, Sven; Wildemann, Brigitte; Senel, Makbule; et al.
Background: There is limited and inconsistent information on the prevalence of cognitive impairment in neuromyelitis optica spectrum disorders (NMOSD). Objective: To assess cognitive performance and changes over time in NMOSD. Methods: This study included data from 217 aquaporin-4-IgG-seropositive (80%) and double-seronegative NMOSD patients. Cognitive functions measured by Symbol Digit Modalities Test (SDMT), Paced Auditory Serial-Addition Task (PASAT), and/or Multiple Sclerosis Inventory Cognition (MuSIC) were standardized against normative data ( N  = 157). Intraindividual cognitive performance at 1- and 2-year follow-up was analyzed. Cognitive test scores were correlated with demographic and clinical variables and assessed with a multiple linear regression model. Results: NMOSD patients were impaired in SDMT ( p  = 0.007), MuSIC semantic fluency ( p  < 0.001), and MuSIC congruent speed ( p  < 0.001). No significant cognitive deterioration was found at follow-up. SDMT scores were related to motor and visual disability ( p Bon  < 0.05). No differences were found between aquaporin-4-IgG-seropositive and double-seronegative NMOSD. Conclusions: A subset of NMOSD patients shows impairment in visual processing speed and in semantic fluency regardless of serostatus, without noticeable changes during a 2-year observation period. Neuropsychological measurements should be adapted to physical and visual disabilities.